2000
DOI: 10.1073/pnas.97.1.303
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability and cytoskeletal defects in oral cancer cells

Abstract: Oral squamous cell carcinomas are characterized by complex, often near-triploid karyotypes with structural and numerical variations superimposed on the initial clonal chromosomal alterations. We used immunohistochemistry combined with classical cytogenetic analysis and spectral karyotyping to investigate the chromosomal segregation defects in cultured oral squamous cell carcinoma cells. During division, these cells frequently exhibit lagging chromosomes at both metaphase and anaphase, suggesting defects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
151
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 233 publications
(166 citation statements)
references
References 42 publications
7
151
0
8
Order By: Relevance
“…Despite the observation that individual OSCC tumor cells express unique karyotypes and at times unique numerical and structural aberrations, many abnormalities within and among malignant cell populations appear to be clonal and remain constant over time in spite of chromosomal instability resulting from chromosome segregation defects. 95 This suggests that clonal abnormalities provide a selective growth advantage for high grade tumors, consistent with the suggestion by Albertson et al. 96 Our cell lines have been examined in our laboratory as late as passage 68 and appear to be remarkably stable.…”
Section: Gene Amplificationsupporting
confidence: 87%
“…Despite the observation that individual OSCC tumor cells express unique karyotypes and at times unique numerical and structural aberrations, many abnormalities within and among malignant cell populations appear to be clonal and remain constant over time in spite of chromosomal instability resulting from chromosome segregation defects. 95 This suggests that clonal abnormalities provide a selective growth advantage for high grade tumors, consistent with the suggestion by Albertson et al. 96 Our cell lines have been examined in our laboratory as late as passage 68 and appear to be remarkably stable.…”
Section: Gene Amplificationsupporting
confidence: 87%
“…Chromosomal bridging in fission yeast is a consequence of compromised kinetochore function (Ekwall et al, 1999) whereas in mammalian cells, it may arise from telomere defects, abnormalities in DNA replication and/or recombination, translocations associated with bi-centromeric chromosomes or overexpression of mitotic checkpoint genes (Harley and Villeponteau, 1995;Menssen et al, 2007;Sotillo et al, 2007). Chromosomal bridging has also been implicated in the creation of micronuclei similar to those reported here ( Figure 5; Saunders et al, 2000) and leads to other structural and numerical abnormalities (Saunders, 2003). Together with previous studies showing that inhibition of cytokinesis in p53À/À mammary epithelial cells leads to the appearance of bi-nucleated cells that are structurally indistinguishable from those of p53 þ / þ cells (Fujiwara et al, 2005), our current findings argue that p53 serves to inhibit or eliminate cells whose genomes have been altered as a result of GpIba overexpression.…”
Section: Discussionsupporting
confidence: 72%
“…This phenomenon has recently been described in several tumour types, including pancreatic and ovarian adenocarcinoma, HNSCC (Gisselsson et al, 2000;Saunders et al, 2000), osteosarcoma, and soft tissue sarcoma (Gisselsson et al, 1999). Such bridges may consist of mitotically unstable chromosomes undergoing repeated breakage-fusion-bridge (BFB) cycles, Figure 3 Multiple centrosomes (g-tubulin, red) in mononucleated (A), binucleated (B), and pentanucleated cells (C) in cases 1, 2, and 8, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Mitotic instability including breakage and/or nondisjunction of chromosomes has been demonstrated in established cell lines from HNSCC (Saunders et al, 2000). Recently, it has been suggested that this type of chromosome instability could be triggered by telomere dysfunction, leading to instability of chromosome termini Gisselsson et al, 2001b).…”
mentioning
confidence: 99%
See 1 more Smart Citation